PENGARUH TERAPI RELAKSASI AUDIO MUROTTAL AL-QUR'AN TERHADAP PERUBAHAN TINGKAT KECEMASAN PADA PASIEN YANG DIRAWAT DI RUANGAN ICU: LITERATUR REVIEW - Yanti Cahyati; Dimas Prakasa; Budi Sanjaya; Adinda Cindy Dayana (LPPM Universitas Bakti Tunas Husada, 2023)
Introduction: Several non-pharmacological therapies are believed to affect the patient's hemodynamics, but therapy based on the Koran has not been widely published. Murottal therapy is a type of music therapy that has a positive effect on listeners, where when someone listens to murottal therapy, it will provide stimulation to the eardrum, which will then be passed on through the auditory nerve to the auditory cortex in the brain so that there will be a decrease in cortisol which can cause a feeling of relaxation. And comfortable. Result: This study aims to determine the effect of murottal al-Qur'an audio relaxation therapy on the anxiety level of patients treated in the ICU to investigate studies that examine the effect of murottal al-Qur'an therapy on the hemodynamic status of patients in intensive care. This study traces papers from google scholar published from 2016 to 2021. Methods: the research used was the PRISMA checklist study to determine study selection and used the PICOS format with the sample. The population studied was patients treated in the ICU room. Discussion: Murottal is one of the music that positively influences listeners. Listening to verses of the Qur'an recited tartil and correctly will bring peace of mind. Conclusion: Al-Qu'an murottal therapy can reduce anxiety in patients treated in the ICU. Murottal Al-Qur'an therapy is one of the interventions nurses can implement to help reduce patient anxiety in the ICU.